1978
DOI: 10.1007/bf01219329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of streptozotocin on erythrocyte and retinal superoxide dismutase

Abstract: Summary. The superoxide dismutase (SOD) activity of rat retinae and erythrocytes was decreased by 30-40% from control levels 5 days after the induction of diabetes with streptozotocin. Homogenates prepared from lungs, liver, brains, aortas, kidneys, whole eyes and lens of streptozotocin-diabetic rats showed no change in SOD activity. Treatment with insulin for three days which restored plasma glucose levels close to normal failed to affect retinal SOD activity in diabetic rats. Retinas (rat and bovine) and ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 20 publications
0
30
1
1
Order By: Relevance
“…From these results, it is most likely that the activity of SOD in the aorta is decreased in the diabetic state. Indeed, it has been found that the activity of SOD in various tissues is decreased in the diabetic state (Crouch et al, 1978;Loven et al, 1982; Matkovics et al, 1982;Cohen, 1995). On the other hand, it has been shown that hydrogen peroxide accelerates NO release (Rubanyi & Vanhoutte, 1986b), activates soluble guanylate cyclase activity, and causes smooth muscle relaxation (Zembowicz et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…From these results, it is most likely that the activity of SOD in the aorta is decreased in the diabetic state. Indeed, it has been found that the activity of SOD in various tissues is decreased in the diabetic state (Crouch et al, 1978;Loven et al, 1982; Matkovics et al, 1982;Cohen, 1995). On the other hand, it has been shown that hydrogen peroxide accelerates NO release (Rubanyi & Vanhoutte, 1986b), activates soluble guanylate cyclase activity, and causes smooth muscle relaxation (Zembowicz et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro inhibition was shown with the purified erythrocyte enzyme as well as with intact erythrocytes or the enzyme extracted from islets. The in vivo inhibition was relatively tissue specific and was observed in erythrocytes and retinae of the rat after injection of streptozotocin or alloxan but not in a number of other tissues studied (5). No information is available concerning the in vivo effects of diabetogenic agents…”
Section: Introductionmentioning
confidence: 99%
“…For example, endogenous antioxidant and scavenging protectors such as vitamin E and glutathione are depleted in diabetes and antioxidant enzymes such as superoxide dismutase and catalase are less active [15][16][17][18].…”
mentioning
confidence: 99%